GENETIC DIVERSITY INDICATORS IN SPP1 GENE OF LOCAL AWASSI EWES IN MIDDLE OF IRAQ - H.A. Al-Huboby , H.A. Al-Huboby; N.N. Al-Anbari , N.N. Al-Anbari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was conducted to identify the genetic diversity indicators of the secreted phosphoprotein 1 (SPP1) gene in flock of local ewe's sheep in middle of Iraq. The sample was made up of 48 ewes and the duration of the study was six months. Genetic polymorphisms were identified and four SNPs (4) variants were obtained. The average allelic abundance (Na) was 2.00, the average number of alleles affected (Ne) was 1.0539, Shannon Guide (I) 0.1163. The average allelic abundance was equal in all the variations studied (2.00) and the number of alleles affected was higher in SNP2 and SNP3, both at (1.0425) compared to SNP1 (1.0211) and SNP4 (1.1096). Obs-Hom and (0.9479) are very close to Exp- Hom and (0.9492). The individual's evidence of persistence within the Fis clan of the G, A, C and T allels of local sheep were -0.0367. The Fit's aggregate stability manual obtained according to SPP1 gene analysis is also -0.0367. Therefore, we can conclude that there is no genetic drift that causes genetic differentiation of the local sheep's sample and this may be due to the large number of rams used by matting, thereby creating an appropriate variation in flock.